Needs Analysis for the Development of a Guided Inquiry-based E-Module on Biodiversity Material - Susanto, Mardomo; Indrowati, Meti; Karyanto, Puguh (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This paper documents the need for developing a guided inquiry-based e-module on biodiversity material for high school students. The research employs a descriptive exploratory approach involving 41 respondents, consisting of biology teachers and grade X students selected using cluster random sampling. Data were collected through questionnaires focusing on the availability, use, and expectations of learning media. The results showed that current biology learning still relies heavily on teacher-centred methods and printed textbooks and lectures, limiting students’ engagement and scientific literacy. Both teachers and students expressed the need for a digital learning media that supports independent learning, encourages active student involvement, and aligns with the guided inquiry approach. The findings support the urgency to develop an interactive e-module that integrates inquiry-based learning steps and can be used flexibly both inside and outside the classroom.